ASSESSMENT OF THE PEROXIDE OXIDATION INDEX OF LIPIDS IN THE ORAL FLUID OF CHILDREN WITH FLUOROSIS IN THE DYNAMICS OF COMPREHENSIVE ORTHODONTIC TREATMENT - Shnaider, D.S.; Dienga, A.E.; Glazunov, O.A.; Skulska, S.V.; Diieva, T.V.; Tsevukh, L.B.; Osadcha, A.O. (World of Medicine and Biology, 2025)
The study was devoted to the effect of a treatment and preventive complex of drugs on the content of malondialdehyde in the oral fluid of children with endemic fluorosis and orthodontic pathology Twenty-five children (6–7 years old) were allocated to a comparison group and a main group. Unstimulated whole saliva was collected at baseline, after one month (pre-bonding), and at 3, 6, and 12 months after bracket placement. Salivary malondialdehyde concentrations were measured spectrophotometrically. Findings indicate that the treatment and preventive complex exerts sustained antioxidative and membrane-protective effects, counteracting the combined oxidative burden of fluorosis and orthodontic pathology.
Keywords: dental fluorosis; malondialdehyde; lipid peroxidation; orthodontic treatment; antioxidants; children; therapeutic-prophylactic complex